Bulgaria : Selected Issues and Statistical Appendix. (IMF Staff Country Reports; Country Report, 2001)
The extensive growth model introduced under central planning in the 1950s resulted in rapid industrialization and initially high growth. The efforts to bring the banking system on a sound footing following the 1996-97 crises have hardened budget constraints, but they have yet to result in a reorientation of banking sector activities toward private sector lending. The following statistical data are presented in detail: industrial sector, services by branches, income accounts, financial performance of state-owned enterprises, monetary survey, the exchange rates, and so on.